2004
DOI: 10.3354/meps280261
|View full text |Cite
|
Sign up to set email alerts
|

Foraging strategies of grey-headed albatrosses Thalassarche chrysostoma: integration of movements, activity and feeding events

Abstract: We identified a range of foraging strategies adopted by grey-headed albatrosses Thalassarche chrysostoma rearing chicks at Bird Island, South Georgia, by simultaneously using satellite telemetry, wet/dry activity recorders and stomach temperature loggers. The albatrosses foraged mostly over oceanic waters, probably associated with the Polar Front north of South Georgia, and also over shelf-slope waters around the Antarctic Peninsula. After leaving the colony, birds commuted to areas with predictable prey conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 41 publications
4
89
0
Order By: Relevance
“…Although several studies found correlations between the distribution of birds and prey (Catry et al, 2004;Weimerskirch et al, 2005;Fauchald and Tveraa, 2006), one study found no relationship between foraging effort and fish stocks (Croll et al, 2006), or only with primary productivity, rather than fish stocks (Grémillet et al, 2008). Thus, species may vary in their responses to food supply in both colonybased reproductive parameters, and biologger-derived foraging parameters.…”
Section: Use Of Biologger-derived Behaviors As Indicators Of Food Supplymentioning
confidence: 96%
“…Although several studies found correlations between the distribution of birds and prey (Catry et al, 2004;Weimerskirch et al, 2005;Fauchald and Tveraa, 2006), one study found no relationship between foraging effort and fish stocks (Croll et al, 2006), or only with primary productivity, rather than fish stocks (Grémillet et al, 2008). Thus, species may vary in their responses to food supply in both colonybased reproductive parameters, and biologger-derived foraging parameters.…”
Section: Use Of Biologger-derived Behaviors As Indicators Of Food Supplymentioning
confidence: 96%
“…1 Box-plots depicting the number of take-offs and landings (per day or night) of Old (N = 18) and Mid-aged (N = 17) Cory's Shearwaters Calonectris diomedea. Differences were tested on logtransformed data (see Table 1 for statistics) 7.5 9.0 M-W U = 100.5 Ornithol (2011) 152:549-555 553 active during the latter (Catry et al 2004;Phalan et al 2007; this study). The disproportionate reduction of activity among old Shearwaters during darkness might reflect a strategy to avoid demanding activities when they are less likely to yield a benefit, given that foraging at night seems to be less profitable for visual predators such as seabirds (Catry et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Differences were tested on logtransformed data (see Table 1 for statistics) 7.5 9.0 M-W U = 100.5 Ornithol (2011) 152:549-555 553 active during the latter (Catry et al 2004;Phalan et al 2007; this study). The disproportionate reduction of activity among old Shearwaters during darkness might reflect a strategy to avoid demanding activities when they are less likely to yield a benefit, given that foraging at night seems to be less profitable for visual predators such as seabirds (Catry et al 2004). An experimental study with Cory's Shearwaters showed that handicapped birds (carrying extra mass) also reduced their activity levels (less time spent flying) during darkness (Passos et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cephalopods are also known as the main prey item for several pelagic predators such as tunas, billfishes, oceanic sharks and cetaceans, which reflect the abundance of cephalopods in the epi and mesopelagic environments. However, how albatrosses locate and catch cephalopods is still subject of much debate (Croxall & Prince 1994, Catry et al 2004, Weimerskirch et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ommastrephids are abundant at the sea surface only at night (Roper & Young 1975). Grey-headed spent 86 -94% of their nighttime sitting on the sea, once diving is chiefly limited by their visual acuity (Huin & Prince 1997, Catry et al 2004.…”
mentioning
confidence: 99%